2004
DOI: 10.1074/jbc.m405372200
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-BARD1 Complexes Are Required for p53Ser-15 Phosphorylation and a G1/S Arrest following Ionizing Radiation-induced DNA Damage

Abstract: BRCA1 is a major player in the DNA damage response. This is evident from its loss, which causes cells to become sensitive to a wide variety of DNA damaging agents. The major BRCA1 binding partner, BARD1, is also implicated in the DNA damage response, and recent reports indicate that BRCA1 and BARD1 co-operate in this pathway. In this report, we utilized small interfering RNA to deplete BRCA1 and BARD1 to demonstrate that the BRCA1-BARD1 complex is required for ATM/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 63 publications
2
107
0
1
Order By: Relevance
“…Supporting the idea that the 3 0 processing machinery is interconnected with the p53 pathway, it has been shown that Rbbp6, a p53-binding protein, and Ku-70 subunit of DNA-PK, which is involved in the BARD1-mediated phosphorylation of p53 Ser15 upon DNA damage (Fabbro et al, 2004), are part of the pre-mRNA 3 0 processing complex ). Other tumor suppressors, such as CSR1 and Cdc73, have also been shown to functionally associate with 3 0 processing factors, such as CPSF3 (Zhu et al, 2009) and CPSF/ CstF (Rozenblatt-Rosen et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Supporting the idea that the 3 0 processing machinery is interconnected with the p53 pathway, it has been shown that Rbbp6, a p53-binding protein, and Ku-70 subunit of DNA-PK, which is involved in the BARD1-mediated phosphorylation of p53 Ser15 upon DNA damage (Fabbro et al, 2004), are part of the pre-mRNA 3 0 processing complex ). Other tumor suppressors, such as CSR1 and Cdc73, have also been shown to functionally associate with 3 0 processing factors, such as CPSF3 (Zhu et al, 2009) and CPSF/ CstF (Rozenblatt-Rosen et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Phosphorylation of BRCA1 on these sites is closely linked to S-phase and G2/M checkpoints (Xu et al, 2001. Several studies also showed that BRCA1 is required for optimal levels of ATM-dependent phosphorylation of p53, c-Jun, Nbs1, Chk2, CtIP and SMC1, although the BRCA1 dependence of some of these phosphorylation events is controversial (Foray et al, 2003;Fabbro et al, 2004;Kitagawa et al, 2004). Kitagawa et al (2004) also showed that BRCA1 is required for focus formation by autophosphorylated ATM.…”
Section: Likely Candidates For Inactivators and Activators Of Atmmentioning
confidence: 99%
“…The proper G1/S checkpoint regulation following DNA damage is mainly due to the p53-mediated induction of p21 waf1 and it has been proposed that BRCA1 expression is necessary for p53 and p21 induction following ionizing radiation (Fabbro et al, 2004), suggesting that the absence of BRCA1 could influence the G1/S cell cycle progression after DNA damage (Fabbro et al, 2004). We thus evaluated the expression of p21 and p53 in parental and YHA6 and 7 MCF-7 cells untreated or exposed for 24 h to cisplatin or bleomycin.…”
Section: Mcf-7 Cells Overexpressing the Hmga1 Protein Are More Sensitmentioning
confidence: 99%